2009
DOI: 10.1007/s11243-009-9214-z
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic and antimicrobial studies of binuclear ruthenium(III) complexes containing bis-β-diketones

Abstract: A series of new binuclear Ru(III) complexes of the type {[RuX 3 (EPh 3 )] 2 (bis-b-dk)} [X = Cl/Br; E = P/ As bis-b-dk = bis(b-diketone)] have been prepared by reacting [RuCl 3 (PPh 3 ) 3 ], [RuCl 3 (AsPh 3 ) 3 ], [RuBr 3 (PPh 3 ) 3 ],[RuBr 3 (AsPh 3 ) 3 ] with bis(b-diketones) in a 2:1 molar ratio in benzene. These complexes have been characterized by physico-chemical and spectroscopic methods. The redox property of the complexes were studied by cyclic voltammetric technique. The complexes were found to be ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 41 publications
1
17
0
1
Order By: Relevance
“…The XRD pattern of silica exhibits sharp peaks indicates its crystalline nature, while broad peak of nanosilica is indicative of amorphous nature . The diffraction pattern of Ru@imine‐nanoSiO 2 demonstrates new peaks at 2θ ≈ 19.06, 28.02, 38.6° and 58.1° corresponding to the (202), (213), (430) and (641) planes of octahedral Ru (III) complex . This difference in the XRD pattern of Ru@imine‐nanoSiO 2 and nanosilica is due to modification on the surface of nanosilica on successful immobilization.…”
Section: Resultsmentioning
confidence: 96%
“…The XRD pattern of silica exhibits sharp peaks indicates its crystalline nature, while broad peak of nanosilica is indicative of amorphous nature . The diffraction pattern of Ru@imine‐nanoSiO 2 demonstrates new peaks at 2θ ≈ 19.06, 28.02, 38.6° and 58.1° corresponding to the (202), (213), (430) and (641) planes of octahedral Ru (III) complex . This difference in the XRD pattern of Ru@imine‐nanoSiO 2 and nanosilica is due to modification on the surface of nanosilica on successful immobilization.…”
Section: Resultsmentioning
confidence: 96%
“…If G < 4.0, considerable exchange coupling might be present and generate the considerable misalignment. In this study, the observed G value of [CuLCl2]2 is 5.4 which explains that the local tetragonal axes are aligned parallel or slightly misaligned and exchange coupling could be worthless [48]. The observed empirical ratio of g| |/A|| value for the dimeric complex [CuLCl 2]2 is 162 which pointed out the octahedral geometry of dimeric [CuLCl2]2 with small distortion.…”
mentioning
confidence: 49%
“…From Table , it is clear that the inhibition diameters of the zinc(II) chelates are higher than that of the respective antibiotics. Such increased activity is attributed in part to the lipophilic nature of the zinc(II) ion in the complexes . However, the enhanced bactericidal activity of the zinc(II) ion upon coordination most probably arises from the contribution of the ligand moiety in the complex.…”
Section: Resultsmentioning
confidence: 99%